THE VOCABULARY LEARNING BEHAVIOR OF ROMANIAN HIGH SCHOOL STUDENTS IN A DIGITAL CONTEXT - COJCNEAN, Diana Maria (Presa Universitară Clujeană, 2017)
This thesis investigates the vocabulary learning behavior of Romanian high school students in a digital context. The research identifies the vocabulary learning strategies used by EFL high school students and focuses on how the choice of vocabulary learning strategies varies across four independent variables: students’ age, gender, academic profile (math‐ICT, humanities, science and economic‐technical) and language program (intensive English, bilingual, normal). These variables are hypothesized to influence learners’ vocabulary behavior.